EVALUATION OF THE TEACHING AND LEARNING PROCESS DURING THE COVID-19 PANDEMIC (CASE STUDY AT SD NEGERI 111 PEKANBARU) - Eka Putri Zulyani; Febri Yuliani (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
Evaluation is a very important part of the learning process. Evaluation is a process carried out to obtain information about success, effectiveness in the learning process. The purpose of this study is to find out how the teaching and learning process at SD Negeri 111 Pekanbaru during the Covid-19 pandemic. The transition of changes in the teaching and learning process carried out online (in the network) to face-to-face is limited to the main reason researchers see how the success and impact of the policy is realized. The implementation of this limited face-to-face learning process is an alternative step taken by the government in responding to the ineffective implementation of the online learning process, especially in the field of basic education. This research is descriptive with a case study approach and the necessary data is primary and secondary data derived from observations, interviews, documentation analyzed by researchers so as to get accurate and clear data about the evaluation of the teaching and learning process during the Covid-19 pandemic. The results of this study show that this limited face-to-face teaching and learning process is better than the teaching and learning process carried out online which is measured from input indicators (resources, infrastructure), processes, outputs (results), and outcomes (impact).Evaluasi merupakan bagian yang sangat penting dalam proses pembelajaran. Evaluasi merupakan proses yang dilakukan untuk memperoleh informasi tentang keberhasilan, efektivitas dalam proses pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana proses belajar mengajar di SD Negeri 111 Pekanbaru selama pandemi covid 19. Adanya transisi perubahan proses belajar mengajar yang dilakukan secara daring (dalam jaringan) ke tatap muka terbatas menjadi alasan utama peneliti melihat bagaimana keberhasilan dan dampak dari kebijakan tersebut terwujud. Penyelenggaraan proses belajar tatap muka terbatas ini merupakan langkah alternatif yang diambil pemerintah dalam menanggapi tidak efektifnya pelaksanaan proses pembelajaran daring terkhususnya pada jejang pendidikan dasar. Penelitian ini bersifat deskriptif dengan pendekatan studi kasus serta data yang diperlukan ialah data primer dan sekunder yang berasal dari observasi, wawancara, dokumentasi yang dianalisis oleh peneliti sehingga mendapatkan data yang akurat dan jelas mengenai evaluasi proses belajar mengajar di masa pandemi covid-19. Hasil dari penelitian ini menunjukkan bahwa proses belajar mengajar secara tatap muka terbatas ini lebih baik dibandingkan dengan proses belajar mengajar yang dilakukan secara daring yang di ukur dari indikator input (sumber daya, infrastruktur), proses, output (hasil), dan outcome (dampak).